Let there be light [videorecording (DVD)] - Sorbo, Kevin; Sorbo, Sam; Sorbo, Sam; Hannity, Sean, 1961-; Warwick, Dionne (Viva Pictures, 2018)
For all his far-reaching fame, Sol Harkens, the world's most famous atheist, is a lonely soul and a lousy part-time dad. After a near death experience challenges his simplest assumptions about this world, Sol finds his purpose and re-imagines his life, in a film that will make you laugh and cry and want to stand up and cheer.